Profil Kebugaran Jasmani Peserta Didik Kelas Khusus Olahraga Daerah Istimewa Yogyakarta - Utomo, Suryo; Komarudin, Komarudin; Cakrawati, Dewi Kiani; Kusumawardhana, Buyung; Oktarifaldi, Oktarifaldi (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2024)
This study aims to evaluate the physical fitness level of students in special sport class program in the Special Region of Yogyakarta. This study used a descriptive research approach and a cross-sectional study design. The sample size of this study consisted of 128 students. This study used a purposive sampling technique to select participants. This study used the Indonesian Physical Fitness Test, explicitly designed for individuals aged 16 to 19, as a measurement tool. The results showed that 29 students (22.6%) were in